Colonic mucosubmucosal elongated polyp: report of a series of 14 cases and review of the literature. Issue 4 (27th April 2016) - Ali, Rola H; Mohammad, Nissreen M; Serra, Stefano; Chetty, Runjan
Abstract : Aims: Most colorectal polyps can be reliably assigned to one of the known polyp categories, but a subset of polyps named colonic mucosubmucosal elongated polyps (CMSEPs) do not fall into any of these categories. First described in the Japanese literature, CMSEPs seem to be under‐recognized in the Western literature. The aims of this study were to describe the clinicopathological features of 14 CMSEPs, discuss potential pathogenetic mechanisms, and increase awareness of this entity among pathologists. Methods and results: Fourteen pedunculated colorectal polyps that met the histopathological criteria for CMSEP (as described by Matake et al . and Alizart et al .) were assessed (12 males and two females; mean age 59.7 years). Five polyps were located in the sigmoid colon, four in the rectum, two in the descending colon, and three in the colon not otherwise specified. Nine of 14 polyps were discovered incidentally: two of nine on routine screening colonoscopy, two of nine on surveillance colonoscopy for inflammatory bowel disease (IBD), and five of nine upon surgical intervention for carcinoma or IBD. None coexisted with diverticular disease. The polyps were long and slender, varied from 5 to 30 mm in length (mean 15.9 mm), and showed a normal‐looking colonic mucosal layer and underlying loose submucosa with thick‐walled and congested blood vessels and lymphatics. Conclusions: CMSEPs show subtle but distinctive pathological features, and occur in normal and diseased colons. Pathologists need to be aware of this entity, to avoid confusion with other more commonly encountered colorectal polyps. With increasing colon cancer screening programmes and surveillance colonoscopy, it is likely that CMSEPs will be encountered more often.